Clarifying the effect of behavioral and clinical factors on traumatic dental injuries in childhood: a hierarchical approach. Issue 3 (25th March 2015) - Kramer, Paulo Floriani; Feldens, Eliane Gerson; Bruch, Cristina Montini; Ferreira, Simone Helena; Feldens, Carlos Alberto
Abstract Aim To explore associations between traumatic dental injuries (TDI) in Brazilian preschool children and clinical, behavioral, and socio‐demographic factors using a hierarchical approach. Material and Methods A cross‐sectional study was conducted involving 1316 children aged 0–5 years at public preschools in the city of Canoas (southern Brazil). Demographic (sex and age), socioeconomic (mother's schooling, income and family structure) and behavioral (use of pacifier, breastfeeding duration and bottle use at 12 months) factors were collected through a questionnaire. TDI (Andreasen criteria) and malocclusion (overjet and anterior open bite) were recorded by trained and calibrated examiners. Poisson regression was employed to determine factors associated with TDI using a hierarchical approach. Results The prevalence of TDI was 13.3%. In the final model, the probability of TDI was 50% higher in children who used a pacifier (PR: 1.50; 95% CI: 1.08–2.10), 77% higher in children with overjet between 3 and 5 mm (PR: 1.77; 95% CI: 1.22–2.57) and nearly threefold higher in children with overjet > 5 mm (PR: 2.73; 95% CI: 1.77–4.20) compared with children with overjet ≤ 2 mm. Additional analysis demonstrated that overjet represented the pathway by which pacifier use was associated with TDI. Conclusion Pacifier use is strongly associated with the occurrence of TDI in the primary dentition, and accentuated overjet represents a pathway to this association. These findings suggest the need for prevention strategies that address early counseling on pacifier use to reduce the occurrence of TDI.